THE ESG AUDIT PLANNING PROCESS AND ITS SPECIFIC ASPECTS (American Journal of Business Management, Economics and Banking, 2026)
In this article, in the context of sustainable development The ESG audit planning process and its specific aspects The research was reviewed and suggestions and recommendations were made.